Heart Full of Soul : An Inspirational Memoir About Finding Your Voice and Finding Your Way - Hicks, Taylor, 1976- and Wild, David, 1961- (New York Crown Publishers, 2007)
The Southern singer recounts his rise from being a member of a small touring Alabama band to being the 2006 winner of the "American Idol" contest and the impact that his victory has had on his life and career
Include Index
Keywords: Singers -- United States -- Hicks, Taylor, 1976-